Pemanfaatan Teknologi Nuklir untuk Meningkatkan Ketahanan Daya Simpan Ikan Laut - Paembonan, Sang Gyn You De; Aisyah, Siti; Rahmadani, Reski; Rizkia, Muliani; Mega Savira Utami, Ni Wayan (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2025)
The use of nuclear technology, particularly irradiation using gamma rays, offers an effective solution for increasing the shelf life of marine fish. This article discusses the physics behind the use of gamma rays from Cobalt-60 and Cesium-137 sources in food irradiation. Cobalt-60 is the most commonly used source of gamma rays because it emits high-energy radiation that effectively penetrates foodstuffs, including marine fish. The irradiation process works by damaging the DNA of microorganisms that cause spoilage and disease through ionizing radiation, thereby extending the shelf life of fish without compromising nutritional quality and taste. The use of Cesium-137, although less common, is also discussed as an alternative source of gamma rays. Irradiation with gamma rays from Cobalt-60 and Cesium-137 has been proven effective in killing pathogenic microorganisms and maintaining the freshness of marine fish for longer. Challenges in implementing this technology, such as initial costs and consumer education, need to be addressed to maximize its benefits. The future prospects for food irradiation are very promising with further research and collaboration between sectors.